RECOGNITION OF FACIAL EXPRESSION IN HUMANS USING IMAGE PROCESSING - Prof.Smita AnnasahebDhon 1, Prof. Amol B. Jagdale 2, Dr.Prashant V. ManeDeshmukh 3 (International Journal of Innovations in Engineering Research and Technology, 2022)
In this facial expression has many real world applications such as medical, human machine interaction and human psychology. This paper elaborates the concept of facial expression using image processing with application of biometric System. Facial expression recognition system have a vital role in numerous areas such as intelligent human computer interaction This proposed system aimed to present and disgusted. The proposed system divides three main task preprocessing; feature extraction last one is classification. In this facial expression recognition that of various facial emotion expression is done by using some extracted features as well as classification is perform by different classifier we select one of them. A well-known viola Jones face detection method is used for human face detection. After face detection feature extraction for eyes and mouth. Then feature selection, centroid of facial features finding, Then obtain features are clustered by using an efficient method named SVM or some other classifier to recognize various human expressions. This process is performed by matlab R2013 (a)after the successful testing with the proposed system facial expression recognition efficiency best obtain from different classifier. Index Terms- Facial feature extraction, face detection, facial expression recognition, Matlab